2011
DOI: 10.1007/978-3-642-21034-1_21
|View full text |Cite
|
Sign up to set email alerts
|

Understanding an Ontology through Divergent Exploration

Abstract: Abstract. It is important that the ontology captures the essential conceptual structure of the target world as generally as possible. However, such ontologies are sometimes regarded as weak and shallow by domain experts because they often want to understand the target world from the domain-specific viewpoints in which they are interested. Therefore, it is highly desirable to have not only knowledge structuring from the general perspective but also from the domainspecific and multi-perspective so that concepts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Future works include an integration of the proposed method and other ontology exploration methods such like our previous works [1,2], application of the system for other ontologies, and improvements of the system through feedbacks from them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future works include an integration of the proposed method and other ontology exploration methods such like our previous works [1,2], application of the system for other ontologies, and improvements of the system through feedbacks from them.…”
Section: Resultsmentioning
confidence: 99%
“…In previous works, the authors proposed divergent exploration of ontology and showed it contribute to the user's understanding of ontology according to their intention and interests [1,2]. Ontology explorations are done through finding concepts related with a focused concept and trace them repeatedly.…”
Section: Introductionmentioning
confidence: 99%
“…Most of semantic web applications use ontologies as vocabularies to describe metadata and are aimed at semantic processing of them [20]. Regarding ontology as the exploration target, the main DBE approache is composed of: (1) the systematized conceptual structure of ontologies and (2) on the fly conceptual structures identification from the ontologies to cope with various dashboard interests.…”
Section: Knowledge-based Dashboard-by-example Frameworkmentioning
confidence: 99%
“…The framework defines six (6) locally-led innovation lifecycle phases; needs, strategy, incubation, localization, evaluation, and creation. It is refined via four (4) [1]. This paper focuses on semantic knowledge management for the SEED framework.…”
Section: Introductionmentioning
confidence: 99%
“…Annotating metadata using terms defined in ontologies enable users to search data across domains (Layer 0-1). A divergent ontology exploration tool can generate comprehensive conceptual maps from user's multiple arbitrary perspectives [4]. The exploration tool allows the user to explore ontologies interactively according to their interests.…”
Section: Introductionmentioning
confidence: 99%